New Paradigm of What Learning Outcomes Are: The Role of Generative AI - Silva, Thomaz E. V. da (Anais do Workshop Uma Tarde na Urca: Encontro Filosófico sobre Informática na Educação (URCA); 2024: Anais do I Workshop Uma Tarde na Urca: Encontro Filosófico sobre Informática na Educação, 2024)
This essay explores the transformative potential of generative AI in redefining learning outcomes and assessment practices in education. We challenge the traditional reliance on grades and standardized tests, advocating for assessments that prioritize knowledge application over recall. The essay also raises critical questions about learning accountability and equity, particularly in the context of AI's impact on underserved communities. By embracing educometrics and focusing on personalized, adaptive learning environments, we argue that AI can enhance both formative and reflective assessment processes, provided that equitable access to these technologies is ensured for all students.